2015
DOI: 10.1071/hc15130
|View full text |Cite
|
Sign up to set email alerts
|

Patient expectations for chronic pain management

Abstract: INTRODUCTION: In New Zealand, one in six people report chronic pain, but the literature indicates only a 30% pain reduction is typically achieved in about half of treated patients. Most patients expecting a cure of their pain, or even substantial pain reduction, are therefore likely to be disappointed. It is important to align patient expectations with this reality. METHODS: This study analysed the responses of 250 patients referred to a Pain Management Centre to the free-text question: 'What are your main goa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
6
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 25 publications
1
6
0
1
Order By: Relevance
“…Bhana and colleagues also found that all pain sensations could not be controlled, and pursuit of a pain free life was unrealistic. 61 …”
Section: Discussionmentioning
confidence: 99%
“…Bhana and colleagues also found that all pain sensations could not be controlled, and pursuit of a pain free life was unrealistic. 61 …”
Section: Discussionmentioning
confidence: 99%
“…As detailed in Table , a significant portion of the patients did not improve. It is known that expectations are a key driver of satisfaction . More time is required with respect to patient education and expectation management if the dual goal of high patient satisfaction and appropriate medical care is desired.…”
Section: Discussionmentioning
confidence: 99%
“…That reduction of pain intensity must precede improvement in these other problems is a common belief for both clinicians 13 and patients. 2,6,24,27 However, there is robust evidence that pain reduction may be accompanied or even preceded by changes in sleep disturbance, function, or affective distress. 4,5,17,18,35,42,45 This body of evidence suggests that although other symptoms may develop after the onset of chronic pain, they may also impede effective recovery from chronic pain once they are present.…”
mentioning
confidence: 99%